PENGARUH EXPERIENTIAL MARKETING DAN BRAND TRUST TERHADAP KEPUASAN PELANGGAN DAN LOYALITAS PELANGGAN HOTEL ARYADUTA DI PEKANBARU - Boby Setiawan Putra; Jushermi '; Deny Danar Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aimed to analysze Experiential Marketing and Brand Trust on Customer Satisfaction and Customer Loyalty. This research was conducted at the customer Aryaduta Hotel Pekanbaru. Where these customers should have more than one time stay at Hotel Aryaduta Pekanbaru. In this study consists of four variables: the dependent variable, the intervening variable and two independent variables. These variables are Customer Loyalty (Y2), Customer Satisfaction (Y1), Brand Trust (X2), and Experiential Marketing (X1). This study was conducted using a sample of 100 people. This study using simple random sampling technique that is making members of the sample of the population was randomly without regard to strata that exist in this population. Thereby done when members of the population considered to be homogeneous. In terms of data analysis, this study using Path Analysis with SPSS (Statistical Package for Social Science) version 20. Based on tests conducted Hypothesis, Results showed that Experiential Marketing and Brand Trust positive and significant impact on the Customer Satisfaction and Customer Loyalty.Keywords: Experiential Marketing, Brand Trust, Customer Satisfaction, Customer Loyalty.